How spiritual leadership and organizational culture influence employee performance? - Fajar Surya Ari Anggara; Alfin Aulia (Universitas Kristen Maranatha, 2021)
Spiritual leadership management is causal leadership for organizations designed to produce educational organizations that are intrinsically motivated. The aim of spiritual leadership is to produce a strategic and empowered vision and value appropriateness of team-level values and people and, in its words, greater responsiveness and organizational productivity. Organizational culture is a perception that is made jointly by members of the organization and must be obeyed by members of the organization or it is called a system created for togetherness. To achieve economic independence, Darussalam Gontor University established a business unit, namely the UNIDA Business Unit (U3). The Darussalam Gontor University Business Unit is one of the business fields owned by the Darussalam Gontor University with employees of different backgrounds. This study aimed to analyze the influence of organizational culture and spiritual leadership on the performance of employees of the Darussalam Gontor University Business Unit. This type of research was a quantitative study with a total of 49 respondents. The population of this study were all employees of the Darussalam Gontor University Business Unit which included managers, staff, and operational employees. The technique used was multiple linear regression analysis techniques. Data obtained through respondents with a survey in the form of a questionnaire and measured using a Likert scale. The results showed that organizational culture has a positive and insignificant effect on employee performance. Meanwhile, spiritual leadership has a positive and significant effect on employee performance.